2020
DOI: 10.3389/fcell.2020.00279
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Death and Promotion of Chondrogenic Differentiation by Fas/FasL in Human Dental Pulp Stem Cells (hDPSCs)

Abstract: Human dental pulp stem cells (hDPSCs) are characterized by high proliferation rate, the multi-differentiation ability and, notably, low immunogenicity and immunomodulatory properties exerted through different mechanisms including Fas/FasL pathway. Despite their multipotency, hDPSCs require particular conditions to achieve chondrogenic differentiation. This might be due to the perivascular localization and the expression of angiogenic marker under standard culture conditions. FasL stimulation was able to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Then, flow cytometry analysis was performed on STRO-1 + /c-Kit + hDPSCs, expanded upon confluence at passage 1, to assess the expression of MSC surface markers. As reported in Figure 1 , STRO-1 + /c-Kit + hDPSCs were labeled positive against CD73, CD90, CD105 and, to a lesser extent CD34, while showing no labeling against CD45 and HLA-DR, in accordance with previous reports [ 27 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Then, flow cytometry analysis was performed on STRO-1 + /c-Kit + hDPSCs, expanded upon confluence at passage 1, to assess the expression of MSC surface markers. As reported in Figure 1 , STRO-1 + /c-Kit + hDPSCs were labeled positive against CD73, CD90, CD105 and, to a lesser extent CD34, while showing no labeling against CD45 and HLA-DR, in accordance with previous reports [ 27 ].…”
Section: Resultssupporting
confidence: 92%
“…In this regard, the aim of the present study was to investigate a novel experimental powder tailored for the development of subgingival prophylaxis treatments, in terms of effects on the biological properties of human dental pulp stem cells (hDPSCs). These stem cells have a peculiar embryological origin from the neural crest, which is common to bone progenitor cells involved in histointegration processes [ 27 ]. In light of these properties, hDPSCs may provide a suitable cell source to assess the cell adhesion, proliferation and osteogenic differentiation when seeded on biomimetic/nanostructured titanium disks previously cleansed with different powders.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, as shown in Figure 4 a, confocal immunofluorescence microscopy also revealed that hDPSCs cultured for 24 h and 4 days on BGMS10 surfaces expressed FasL, a key marker related to stem cells immunomodulatory abilities. As well known from the literature, mesenchymal stem cells and hDPSCs as well are characterized by immunomodulatory properties that can be exerted through different mechanisms, including the Fas/FasL pathway and soluble factors [ 41 , 45 , 46 ]. It is noteworthy that when cultured on BGMS10, hDPSCs not only maintained the expression of stemness markers but also were still positively labeled against FasL.…”
Section: Resultsmentioning
confidence: 99%
“…After dental pulp digestion, the cells obtained are a heterogeneous cell population containing different cell types, among which a stem cell niche can be isolated through immune-selection against stemness markers c-Kit, the tirosin-kinase receptor of stem cells factor, and STRO-1, an antigen present in a stromal cell population containing osteogenic precursors [ 35 , 36 , 37 ]. As reported in literature, hDPSCs are characterized by a high proliferation rate, low immunogenicity and immunomodulatory properties, but they also own the capacity to differentiate into different cytotypes such as osteogenic, chondrogenic, adipogenic, myogenic and neural lineages [ 38 , 39 , 40 , 41 ]. Moreover, previous studies widely reported the regenerative potential of hDPSCs in vivo, when applied to animal models of critical size bone defects [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation